1984
DOI: 10.1113/expphysiol.1984.sp002793
|View full text |Cite
|
Sign up to set email alerts
|

The Dependence of Exocrine Pancreatic Secretion on Insulin in Sheep

Abstract: SUMMARYExocrine pancreatic secretion, blood insulin, glucose and free fatty acid concentrations were measured on days 1, 4 and 5 of a 5 d experimental period. Sheep were treated with alloxan (day 2) and insulin (day 5). The volume of pancreatic juice decreased markedly in the diabetic state and returned to the initial value after insulin treatment. The daily secretion of lipase and amylase decreased during development of diabetes. Injection of insulin restored the secretion of lipase but not amylase. It is sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…In the pancreas, insulin potentiates acetylcholine-evoked amylase release (Singh, 1985), cholecystokinin-stimulated secretion (Saito et al, 1980), and the response to pancreozymin (Kanno and Saito, 1976). Finally, Pierszynowski and Barej (1984) reported that pancreatic secretion in sheep is insulin-dependent. Interestingly, insulin by itself had no secretary effects, suggesting that it may play an important role in maintaining normal exocrine cell function through permissive effects on agonist-response coupling.…”
Section: Resultsmentioning
confidence: 94%
“…In the pancreas, insulin potentiates acetylcholine-evoked amylase release (Singh, 1985), cholecystokinin-stimulated secretion (Saito et al, 1980), and the response to pancreozymin (Kanno and Saito, 1976). Finally, Pierszynowski and Barej (1984) reported that pancreatic secretion in sheep is insulin-dependent. Interestingly, insulin by itself had no secretary effects, suggesting that it may play an important role in maintaining normal exocrine cell function through permissive effects on agonist-response coupling.…”
Section: Resultsmentioning
confidence: 94%
“…(), who reported that regulation of abomasal infusion of starch and/or casein to α‐amylase secretion in steers was not insulin dependent. In addition, in diabetic sheep, insulin administration did not result in α‐amylase secretion returning to normal level (Pierzynowski and Barej, ). These results suggested that the effect of leucine on α‐amylase secretion was not dependent on the change in blood insulin in ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible reason for the greater pancreatic α‐amylase activity in our milk‐fed pre‐ruminant kids is that it was stimulated by the higher insulin levels, as occurs in rats, where plasma insulin level increases just before weaning, enhancing pancreatic functional development (Kinouchi et al., 1998, 2000). It was suggested some time ago that insulin plays an important role in the regulation of pancreatic juice production in ruminants (Pierzynowski and Barej, 1984). The present study confirms that plasma insulin level and pancreatic α ‐amylase activity are strongly correlated, around weaning.…”
Section: Discussionmentioning
confidence: 99%